2023
DOI: 10.1186/s12885-023-11236-z
|View full text |Cite|
|
Sign up to set email alerts
|

Exploring the prognostic significance of PKCε variants in cervical cancer

Sameen Zafar,
Khushbukhat Khan,
Yasmin Badshah
et al.

Abstract: Background Protein Kinase C-epsilon (PKCε) is a member of the novel subfamily of PKCs (nPKCs) that plays a role in cancer development. Studies have revealed that its elevated expression levels are associated with cervical cancer. Previously, we identified pathogenic variations in its different domains through various bioinformatics tools and molecular dynamic simulation. In the present study, the aim was to find the association of its variants rs1553369874 and rs1345511001 with cervical cancer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 88 publications
0
1
0
Order By: Relevance
“…After publication of this article [ 1 ], the authors reported that in this article the author name ‘Suhail Razak’ was incorrectly written as ‘F. Suhail Razak’.…”
mentioning
confidence: 99%
“…After publication of this article [ 1 ], the authors reported that in this article the author name ‘Suhail Razak’ was incorrectly written as ‘F. Suhail Razak’.…”
mentioning
confidence: 99%